2015
DOI: 10.1177/0954411915599801
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on surgical navigation for epiduroscopic laser neural decompression

Abstract: Epiduroscopic laser neural decompression is an emerging therapeutic modality to treat lumbar spine pathologies including chronic low back pain, spinal stenosis, and disk herniation via catheter insertion followed by laser ablation of the lesion. Despite the efficacy of epiduroscopic laser neural decompression, excessive radiation doses due to fluoroscopy during epiduroscopic laser neural decompression have limited its widespread application. To address the issue, we propose a surgical navigation system to assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…According to previous studies, the clinical or surgical outcomes of SELD were found to be favorable in various lumbar spine diseases [3][4][5][6][7][12][13][14][15][16][17]. In particular, several recent papers regarding the clinical outcome of SELD for disc herniation have reported that the clinical outcome was favorable as there was signi cant improvement in low back pain or radiating leg pain, patient satisfaction rate of more than 70%, and low rates of surgical failure or recurrence [8,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the clinical or surgical outcomes of SELD were found to be favorable in various lumbar spine diseases [3][4][5][6][7][12][13][14][15][16][17]. In particular, several recent papers regarding the clinical outcome of SELD for disc herniation have reported that the clinical outcome was favorable as there was signi cant improvement in low back pain or radiating leg pain, patient satisfaction rate of more than 70%, and low rates of surgical failure or recurrence [8,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2000s, in the early days of SELD, some reports have suggested its clinical application in various lumbar spinal diseases to not only disc herniation but also adhesion or fibrosis around nerve roots, failed back surgery, and even spinal stenosis [6][7][8][9][10][11][12][13][14][15]. Based on the principle of using lasers to condense hydrated disc herniation and the accumulated results of the previous literature, the indications of SELD were narrowed to soft disc herniations [16].…”
Section: Introductionmentioning
confidence: 99%
“…SELD is a very successful method in the treatment of chronic low back and/or radicular pain due to spinal disorders. It provides treatment by eliminating the pathology in the epidural space (such as protruded disc material or epidural adhesion and fibrosis around nerve roots) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The aim of this study is to share our SELD experience for the treatment of patients with mild to moderate soft lumbar disc herniation with low back and/or radicular pain who have not had low back surgery and have no back surgery indication.…”
Section: Introductionmentioning
confidence: 99%